2019
DOI: 10.1002/phar.2225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neuromuscular Blocking Agents on Sedation Requirements in Trauma Patients with an Open Abdomen

Abstract: The appropriate level of sedation in patients with an open abdomen following damage control laparotomy (DCL) is debated. Chemical paralysis with neuromuscular blocking agents (NMBAs) has been used to decrease time to abdominal closure. We sought to evaluate the effect of NMBA use on sedation requirements in patients with an open abdomen and to determine the effect of sedation on patient outcomes. A retrospective cohort study was conducted at an American College of Surgeons’ verified level 1 trauma center. Adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Patients receiving NMBA also required more sedation (typically with propofol) than non-NMBA patients, but not more analgesia (typically with fentanyl). Furthermore, the group noted that increased cumulative propofol dose was associated with a decrease in DF/CF-ICU days, corroborating the information in our study [15]. In our series, only three patients underwent treatment with paralytic infusion, all of whom were in the LE group.…”
Section: Multivariate Cox Regression Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Patients receiving NMBA also required more sedation (typically with propofol) than non-NMBA patients, but not more analgesia (typically with fentanyl). Furthermore, the group noted that increased cumulative propofol dose was associated with a decrease in DF/CF-ICU days, corroborating the information in our study [15]. In our series, only three patients underwent treatment with paralytic infusion, all of whom were in the LE group.…”
Section: Multivariate Cox Regression Analysissupporting
confidence: 91%
“…They also published data indicating that chemical paralysis did not affect time to DFC after trauma DCL, with no significant difference in mortality [14]. Additionally, their study showed that patients with neuromuscular blockade had higher sedation requirements [15].…”
Section: Introductionmentioning
confidence: 97%
“…This change was not a clinical effect and required no vasopressor agents. Using an appropriate NMBA did not affect the extubation time, but it did reduce the stress reaction [28]. cis-Atracurium did not cause harmful autonomic nervous system effects and resulted in reduced secretion of histamine.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, administration of additional doses of propofol and sufentanil was needed to achieve satisfactory insertion. The combination of an appropriate dose of muscle relaxants can improve laryngeal mask placement without increasing the incidence of associated adverse reactions, while reducing the amount of propofol or sufentanil anaesthetics and reducing their inhibitory effect on the circulation [27]. Without the use of muscle relaxants, it is necessary to increase the depth of anaesthesia, which prolongs the time of the patient's recovery of consciousness.…”
Section: Discussionmentioning
confidence: 99%